2019
DOI: 10.3390/nu11081958
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Plants with Immunomodulatory Properties during Pregnancy and Lactation—Maternal and Offspring Health Effects

Abstract: A pregnant woman’s diet consists of many products, such as fruits, vegetables, cocoa, tea, chocolate, coffee, herbal and fruit teas, and various commercially available dietary supplements, which contain a high number of biological active plant-derived compounds. Generally, these compounds play beneficial roles in women’s health and the development of fetus health. There are, however, some authors who report that consuming excessive amounts of plants that contain high concentrations of polyphenols may negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 124 publications
(138 reference statements)
1
14
0
Order By: Relevance
“…[ 25–29 ] Recently, many researchers pointed that prenatal malnutrition was closely linked with development of multiple organs via different mechanisms in offspring. [ 30–33 ] In the present study, we first validated that prenatal high‐sucrose diet increased maternal weight before delivery, but it had no effect on the fetal number. Consistent with a population‐based cohort study with 40 years of follow‐up investigated that prenatal hyperglycemia increased rates of early onset cardiovascular diseases from childhood to early adulthood, [ 34 ] our previous data confirmed that prenatal high sucrose impaired the micro‐vascular function of adult and aged offspring.…”
Section: Discussionsupporting
confidence: 51%
“…[ 25–29 ] Recently, many researchers pointed that prenatal malnutrition was closely linked with development of multiple organs via different mechanisms in offspring. [ 30–33 ] In the present study, we first validated that prenatal high‐sucrose diet increased maternal weight before delivery, but it had no effect on the fetal number. Consistent with a population‐based cohort study with 40 years of follow‐up investigated that prenatal hyperglycemia increased rates of early onset cardiovascular diseases from childhood to early adulthood, [ 34 ] our previous data confirmed that prenatal high sucrose impaired the micro‐vascular function of adult and aged offspring.…”
Section: Discussionsupporting
confidence: 51%
“… 201 Dietary polyphenolic compounds such as flavonoids have been shown to have beneficial effects on host defense reactions and inhibit the transcription factor, NF-kB, from producing pro-inflammatory cytokines. 202 , 203 544…”
Section: Mitigation and Therapeutic Intervention Of Covid-19-induced mentioning
confidence: 99%
“…Moreover, it has been pointed out that high consumption of green tea is associated with low serum folate levels during pregnancy and an increased risk of neural tube defects [ 198 ] and case reports of severe anemia after consumption of large amounts of tea have been described [ 214 , 215 ]. In agreement, Camellia sinensis products are among the herbal extracts used to enhance immune system function for which the safety should be determined in pregnancy [ 216 ]. It has recently been pointed out that pregnant women are under-represented in clinical studies, and there is a need for more evidence with respect to drug and nutraceuticals safety and pharmacokinetics [ 217 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%